The Influence of Ethical Leadership on Managerial Performance: Mediating Effects of Mindfulness and Corporate Social Responsibility - WILLIAMS, John J. (Institutional Knowledge at Singapore Management University, 2016)
In a continuing world of corporate misdeeds and unscrupulous decision making, much of the management and academic literatures points to the incomplete knowledge of the consequences of ethics leadership. One of the bastions of ethics gatekeeping in the firm is the CFO but remarkably scant information can be found on their perceptions concerning ethics leadership. This study addresses this void by examining mindfulness and corporate social responsibility (CSR) initiatives as new mediating linkages in comprehending the influence of ethics leadership on managerial performance. Findings reveal that ethical leadership is positively associated with CSR initiatives which, in turn, operate to enhance managerial performance. Simultaneously, ethical leadership manifests a significant positive relationship with mindfulness but, surprisingly, there is no corresponding relationship with managerial performance. Instead, mindfulness indirectly influences managerial performance through the intervening effects on CSR initiatives. These findings suggest that firms can acquire better managerial performance by focusing efforts on CSR strategies, bringing cognitive processes of mindfulness to bear on these actions, and grooming ethics leadership. In addition, the results offer researchers new relationships to model in the leadership domain.